Objective Good Faith and Mortgage Executory Power in Indonesian Auction Law (Study of Decision Number 43/Pdt.G/Plw/2020/PN Srh): Itikad Baik Objektif dan Kekuatan Eksekutorial Hak Tanggungan dalam Hukum Lelang Indonesia (Studi Putusan Nomor 43/Pdt.G/Plw/2020/PN Srh) - Wardani, Kayla; Nurrachman, Alfan Dzikria (Academia Open, 2026)
General Background: Mortgage execution auctions are designed to provide legal certainty for creditors and buyers when debtors fail to fulfill secured credit obligations. Specific Background: In Indonesian auction practice, conflicts may arise when debtors challenge the underlying credit agreement after an auction buyer has completed lawful procedures and obtained rights over the collateral object. Knowledge Gap: Existing studies have discussed auction buyer protection, executory power, and good faith separately, but an integrated normative framework for resolving conflicts between ex ante mortgage execution and ex post debtor claims remains limited. Aims: This study aimed to analyze legal protection for good faith buyers in mortgage execution auctions and examine judicial reasoning in Decision Number 43/Pdt.G/Plw/2020/PN Srh. Results: Using normative legal research with conceptual and case approaches, the study found that buyer protection is constructed through layered norms, including preventive protection through procedural transparency and repressive protection through execution mechanisms. The court confirmed the executory power of mortgage certificates, applied objective good faith under Supreme Court Circular Letter Number 4 of 2016, and separated credit disputes from enforcement proceedings. Novelty: This study integrates mortgage law, civil law, Supreme Court policy, and judicial reasoning to clarify objective good faith standards in execution auctions. Implications: The findings provide practical guidance for judges and buyers while strengthening legal certainty in collateral enforcement. Highlights: Layered safeguards combine procedural clarity and enforcement remedies. Verification duty became central in assessing buyer conduct. Judicial reasoning separated credit conflict from collateral enforcement. Keywords: Mortgage Rights, Execution Auction, Good Faith Buyer, Legal Protection